2022
DOI: 10.1088/2058-6272/ac6571
|View full text |Cite
|
Sign up to set email alerts
|

Micro-impulse and plasma plume produced by irradiating aluminum target with nanosecond laser pulses in double-pulse scheme

Abstract: The micro-impulse generated by ablating aluminum target in double-pulse laser bursts with different interpulse delays was investigated using the torsion pendulum. The plasma plume was simultaneously visualized using high-speed photography to analyze the coupling mechanism of the ablation impulse. The experiment was carried out using the pulsed laser with the pulse width of 8 ns and the wavelength of 1064 nm. The experimental results show that the impulse with an interpulse delay of 60 ns is roughly 60% higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…According to previous research [10], it was found that interpulse delay time has an important influence on the impulse characteristics in double-pulse mode. When the total energy is 200mJ, the impulse shows significantly different characteristics at interpulse delays of 80ns and 300ns.…”
Section: Ablation Impulsementioning
confidence: 94%
“…According to previous research [10], it was found that interpulse delay time has an important influence on the impulse characteristics in double-pulse mode. When the total energy is 200mJ, the impulse shows significantly different characteristics at interpulse delays of 80ns and 300ns.…”
Section: Ablation Impulsementioning
confidence: 94%
“…In recent years, the thrust properties generated by pulsed laser ablation of solid targets have been extensively studied [8][9][10][11]. The thrust performance of LAP is usually evaluated using the impulse coupling coefficient C m , which is the ratio of the impulse generated by laser ablation to the incident laser energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…This special issue is organized from the papers presented in the CEPC 2021. Interested readers can find the papers concerning investigations of plume thermal effect of the LIPS-200 ion thruster [1], the characteristics of non-Maxwellian magnetized sheath in Hall thruster acceleration region [2], the effect of anode axial position on the performance of a miniaturized cylindrical Hall thruster with a cusptype magnetic field [3], early experimental investigation of the C12A7 hollow cathode fed on iodine [4], experimental study on the degradation of the C12A7 hollow cathode [5], numerical simulation of the start-up process of a miniature ion thruster [6], micro-impulse and plasma plume produced by irradiating aluminum target with nanosecond laser pulses in double-pulse scheme [7], simulation of * Author to whom any correspondence should be addressed.…”
mentioning
confidence: 99%